Can Bus On-demand be Attractive in Suburban Areas: A Case Study in Gothenburg - Smilevska , Natalie; Wallin, Vera (My University, 2024)
This master thesis has investigated in how to reduce the use of private cars to travel more sustainably during everyday traveling. The study has focused on bus on demand services to see if it can be a suitable substitute for private cars in suburban areas of Gothenburg. Compared to a normal bus, a bus on-demand is a minibus that can pick up passengers at either a bus stop or a virtual bus stop close to the passenger’s home. Bus on-demand costs the same as a normal bus ticket and ensures that passengers in the same area are picked up with the same minibus. The master thesis has investigated the attitude towards bus on-demand, travel mode choice behavior, and the potential for using bus on-demand in Gothenburg’s suburban areas. This has been done by creating a survey and sending it out to various respondents. In the survey, respondents had to answer which mode of transport they had chosen where time and cost differed. There were four different travel modes, bus on-demand, public transport, shared bicycle/e-scooter, and private car with two different weather scenarios. The results of the survey were applied in Python to obtain coefficients which were then used in probability calculations. The results indicated that individuals are more willing to choose a private car over bus on-demand. This preference can be attributed to the perceived cost-effectiveness and time efficiency of cars. Additionally, respondents’ attitude towards adopting a new travel mode and their existing travel habits significantly influenced their preferences. Several other factors also contributed to this trend. However, bus on-demand have the potential to transform public transportation by providing enhanced flexibility, efficiency, accessibility, and sustainability. Implementation of bus on-demand services is expected to decrease the number of cars in urban areas. Thereby reducing carbon dioxide emissions and contributing to the development of more sustainable urban environments for future generations.
Keywords: Bus on-demand; Gothenburg; Habits; Mode choice behavior; Suburban areas; Sustainable travel; Travel mode